Diagnostic challenges and management advances in cytochrome P450 oxidoreductase deficiency, a rare form of congenital adrenal hyperplasia, with 46, XX karyotype - Wang, Chunqing; Tian, Qinjie (Frontiers in Endocrinology, 2023)
Cytochrome P450 oxidoreductase deficiency (PORD) is a rare form of congenital adrenal hyperplasia that can manifest with skeletal malformations, ambiguous genitalia, and menstrual disorders caused by ytochrome P450 oxidoreductase (POR) mutations affecting electron transfer to all microsomal cytochrome P450 and some non-P450 enzymes involved in cholesterol, sterol, and drug metabolism. With the advancement of molecular biology and medical genetics increasing numbers of PORD cases were reported and the clinical spectrum of PORD was extended with researches on underlying mechanisms of phenotype-genotype correlations and optimum treatment. However, diagnostic challenges and management dilemma still exists because of unawareness of the condition, the overlapping manifestations with other disorders, and no clear guidelines for treatment. Delayed diagnosis and management may result in improper sex assignment, loss of reproductive capacity because of surgical removal of ruptured ovarian macro-cysts, and life-threatening conditions such as airway obstruction and adrenal crisis. The clinical outcomes and prognosis include early death due to developmental malformations or adrenal crisis, bilateral oophorectomies after spontaneous rupture of ovarian macro-cysts, genital ambiguity, abnormal pubertal development and nearly normal phenotype with successful pregnancy outcomes by assisted reproduction. So timely diagnosis including prenatal diagnosis and appropriate management is essential to improve patients' outcomes. However, even in cases with conclusive diagnosis, comprehensive assessment is needed to avoid severe complications, such as chromosomal test to help sex assignment and evaluation of adrenal function to detect partial adrenal insufficiency. In recent years it has been noted that proper hormone replacement therapy can lead to decrease or resolve of ovarian macro-cysts and healthy babies can be delivered by in vitro fertilization and frozen embryo transfer following adequate control of multiple hormonal imbalances. Treatment may be complicated with adverse effects on drug metabolism caused by POR mutations. Unique challenges occur in female PORD patients such as ovarian macro-cysts prone to spontaneous rupture, masculinized genitalia without progression after birth, more frequently affected pubertal development, and impaired fertility. So this review focuses only on 46, XX PORD patients to summarize the potential molecular pathogenesis, differential diagnosis of classic and non-classic PORD and tailoring therapy to maintain health, avoid severe complications and promote fertility.